Al-Istijābah al-Taʼammulīyah al-Murtabiṭah bi al-īmān fī al-Siyāqāt al-Bīʼīyah al-ṭabīʻīyah wa al-ḥaḍariyyah: Dirāsah Kammīyah - alkhudhayr, manar (Universitas Islam Negeri Ar-Raniry, 2026)
This study aimed to measure the level of faith-related contemplative response across natural and urban environmental contexts, addressing the scarcity of quantitative studies on this topic. The study adopted a quantitative descriptive approach using a 26-item questionnaire administered electronically to a sample of 134 participants. The findings revealed a high level of faith-related contemplative response in natural environments (M = 4.35, SD = 0.57), compared with a moderate level in urban environments (M = 2.79, SD = 0.70). No statistically significant differences were found according to place of residence (p > 0.05). The study contributes to the literature by providing a quantitative assessment of the relationship between environmental context and faith-related contemplative response, thereby expanding research at the intersection of environmental and faith-based studies.